Research on the problem of landmines and explosive remnants of war worldwide and methods of demining - Dzenan Cosic; Alan Catovic (Defense and Security Studies)
The study addresses the global issue of landmines, with a particular focus on the challenges in Bosnia and Herzegovina. The research is grounded in precise data and facts from institutions and accredited demining organizations. The study further concentrates on innovative and highly effective detection methods, specifically for areas with challenging topography like Bosnia and Herzegovina, concluding with an innovative application of GPR and LiDAR radar technologies. Additionally, it explores the most effective method for mine removal, and mechanical demining, providing a detailed overview of the operation and characteristics associated with this approach. Conclusively, the study proposes the most efficient solution: a combined system of flails and tillers that alternately complement each other to achieve complete mine clearance.